Mapping the thematic evolution in Communication over the first two decades from the 21st century: A longitudinal approach - Hernandez-Cruz, Netzahualcoyotl (Iberoamerican Journal of Science Measurement and Communication, 2021)
This study offers an overview of the thematic structure in Communication during the first two decades of the 21st century, 2001-2010 and 2011-2020. The included work mapped author keywords and keywords plus of citable articles published in the Journal Citation Reports-2019 edition. A longitudinal perspective was employed to visualize the thematic evolution. Four predominant thematic areas were evidenced in both periods: (1) Speech and Language, (2) Commercial Communication, (3) Health Communication, and (4) Organizational Communication. There were four topics reflecting the formation of substantial research areas during the second decade, such as (1) Science Communication, (2) Scholarly Publishing, (3) Mental Health and Interpersonal Relationships, and (4) Crime and Violence. In general, from the first to the second decade, the technological dimension ceased to be predominant, and instead, there was a more significant presence of themes that responded to a socio-psychological dimension.